Man, a Creature Unteachable. About the Prose Collection Dom Pre Jeleňa by Dominika MoravčíKová - Urbaničová, Zuzana (Bohemica Olomucensia, 2024)
In this paper, we analyse a collection of short stories entitled Dom pre jeleňa (2002) by the author Dominika Moravčíková, who has already drawn attention to herself with her literary debut, a collection of poems, Deti Hamelnu (2020). In both collections, we can observe similar authorial practices, thematic focus, but also specifics analogous to a distinct movement in contemporary Slovak literature.
Keywords: Dominika Moravčíková; Dom pre jeleňa; contemporary Slovak prose